2019
DOI: 10.14710/rotasi.21.3.147-154
|View full text |Cite
|
Sign up to set email alerts
|

Studi Eksperimental dan Simulasi Numerik Karakteristik Aerodinamika Airfoil NACA 4412

Abstract: The objective of this study is to investigate the aerodynamics characteristic of airfoil NACA 4412 based on experiment and numerical simulation. A 3D airfoil with chord length (C) of 100 mm and span-width (S) of 200 mm was fabricated in order to be tested by subsonic wind tunnel at inlet air velocity of 10 m/s, whereas numerical study was realised by 2D airfoil reffering to geometrics in the experiment. The structured mesh with 810,000 elements number was constructed by Gambit meshing tools up to reach the nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…The aspect ratio (AR) of the foil is 7, where AR is defined as the ratio of the span (𝑠) to the chord (𝑐). Prior research on the NACA 4412 indicated that the angle of attack at which the highest lift-to-drag ratio is achieved is between 4° and 6° [34,35]. Hence, the foils were adjusted at an angle of attack of 5.25°, measured in a counterclockwise direction from the vessel's course direction, corresponding to the positive xaxis.…”
Section: Modelling Meshing and Boundary Conditionmentioning
confidence: 99%
“…The aspect ratio (AR) of the foil is 7, where AR is defined as the ratio of the span (𝑠) to the chord (𝑐). Prior research on the NACA 4412 indicated that the angle of attack at which the highest lift-to-drag ratio is achieved is between 4° and 6° [34,35]. Hence, the foils were adjusted at an angle of attack of 5.25°, measured in a counterclockwise direction from the vessel's course direction, corresponding to the positive xaxis.…”
Section: Modelling Meshing and Boundary Conditionmentioning
confidence: 99%
“…Sedangkan memperbesar sudut α, berpengaruh terhadap terjadinya peningkatan nilai Cp pada lower surface airfoil dan penurunan nilai Cp pada upper surface airfoil. Adapun pada kajiannya, Effendy fokus pada investigasi karakteristik aerodinamika airfoil NACA 4412 dengan melakukan ekserimen pada subsonic wind tunnel dan simulasi numerik [4]. Simulasi dikerjakan dengan memodelkan airfoil 2D, mesh terstruktur dan model turbulensi Spalart Allmaras (SA) dengan memvariasikan sudut serang antara -5° hingga 20° dengan kecepatan aliran 10 m/s.…”
Section: Pendahuluanunclassified
“…Perubahan sudut serang airfoil memainkan peran sangat penting terhadap karakteristik aerodinamika aliran, seperti koefisien lift, koefisien drag, rasio lift-drag(L/D), koefisien tekanan dan profil aliran [2]. Pada kecepatan yang tetap gaya angkat akan meningkat seiring dengan peningkatan sudut serang hingga mencapai nilai maksimumnya dan kemudian tiba tiba turun, fenomena ini disebut stalling [1].…”
Section: Pendahuluanunclassified